HUBUNGAN BEBAN KERJA TERHADAP KELELAHAN KERJA BERDASARKAN POSISI JABATAN PADA PEGAWAI DINAS PERINDUSTRIAN DAN PERGADANGAN - Eti Varina, Eka Lailita; Hanan, Siti; Dwiyanti, Agustina (Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
Employees in the industrial sector have diverse job types encompassing both internal and external activities. The daily working hours are 8 hours and 30 minutes for five days a week. Excessive workloads can lead to overuse of energy and cause overstress or fatigue. This study aims to determine the levels of mental workload, work fatigue, and the relationship between mental workload and fatigue. The method used to measure mental workload is the NASA-TLX questionnaire, while work fatigue is measured using the IFRC questionnaire. The researchers employed a cross-sectional approach. Based on the calculation of mental workload by job position, the scores were as follows: Head of Division - 81.33, Head of Section - 72.57, Civil Servants - 71.5, and Non-Permanent Employees (TKK/TKS) - 71. The calculation of work fatigue resulted in scores of 70 for the Head of Division, 76 for the Head of Section, 70.66 for Civil Servants, and 68 for Non-Permanent Employees (TKK/TKS). The Pearson product-moment correlation test (alpha < 0.05) or (0.003 < 0.05) concluded that there is a relationship between mental workload and work fatigue.